2022
DOI: 10.1111/head.14377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern and response to treatment of primary stabbing headache: Retrospective case series study from a Portuguese tertiary hospital

Abstract: Objectives This retrospective case series study aimed to investigate the demographic and clinical patterns of primary stabbing headache (PSH). In addition, we tried to identify subgroups of treatment responses in a neurology outpatient consultation at a Portuguese tertiary hospital. Methods Clinical records were retrospectively reviewed and patients meeting the International Classification of Headache Disorders, 3rd edition, criteria for PSH were identified from January 2014 to December 2020. We collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is now accepted that PSH occurs in an extratrigeminal location in approximately 70–80% of PSH patients (5,16,17,20,21), in contrast to earlier studies where anterior locations such as the orbital, supraorbital, frontal, and temporal regions were common sites of pain in patients with PSH (1,2). A recent clinic-based study reported a lower prevalence of extratrigeminal stabs (53%) in 32 patients (22). Stabs can be multifocal and migrating from one area to another, which has been reported in 23–64% of patients with PSH (1,2,5,17,20,22).…”
Section: Clinical Manifestationmentioning
confidence: 98%
See 4 more Smart Citations
“…It is now accepted that PSH occurs in an extratrigeminal location in approximately 70–80% of PSH patients (5,16,17,20,21), in contrast to earlier studies where anterior locations such as the orbital, supraorbital, frontal, and temporal regions were common sites of pain in patients with PSH (1,2). A recent clinic-based study reported a lower prevalence of extratrigeminal stabs (53%) in 32 patients (22). Stabs can be multifocal and migrating from one area to another, which has been reported in 23–64% of patients with PSH (1,2,5,17,20,22).…”
Section: Clinical Manifestationmentioning
confidence: 98%
“…A recent clinic-based study reported a lower prevalence of extratrigeminal stabs (53%) in 32 patients (22). Stabs can be multifocal and migrating from one area to another, which has been reported in 23–64% of patients with PSH (1,2,5,17,20,22). In patients with migraine, stabs tend to be localized to areas where migraine attacks frequently occur, and can sometimes occur during migraine attacks.…”
Section: Clinical Manifestationmentioning
confidence: 98%
See 3 more Smart Citations